Концептуальный психолого-педагогический подход к развитию психологии личности студента в учебно-воспитательном процессе технического университета - Романовский, Александр Георгиевич (НТУ "ХПИ", 2011)
On the basis of the concept of psychological and pedagogical approach a system of psychological and professional criteria, development of which during training and educational process of Technical University enable us to form psychology of students as future professionals of psychological and engineering elite is highlighted in the article.
Keywords: психолого-педагогические критерии; личность студента университета; уровни развития личности; духовность; "творческое начало"